STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN KEDISIPLINAN GURU DI MTs MADINAH AL-MUNAWWARAH - Fauzan, Hafid; Mustamin; Martini; Ahmad; Muh Azhar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the level of teacher discipline, the leadership strategies of the madrasah principal, as well as the supporting and inhibiting factors in improving teacher discipline at MTs Madinah Al-Munawwarah Tomoni, East Luwu Regency. This research employed a qualitative method with a phenomenological approach. The research subjects consisted of the madrasah principal and teachers of MTs Madinah Al-Munawwarah, totaling eight informants. Data were collected through interviews, observations, and documentation, while data analysis was carried out using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The results of the study indicate that teacher discipline at MTs Madinah Al-Munawwarah is generally in a fairly good category, as reflected in attendance, punctuality, teaching preparedness, and compliance with madrasah regulations, although a small number of teachers are still inconsistent. The leadership strategies implemented by the madrasah principal to improve teacher discipline include routine coaching, habituation of punctuality, exemplary leadership, persuasive communication, strengthening regulations and monitoring, and providing appreciation for disciplined teachers. Supporting factors in improving teacher discipline include teachers’ awareness of professional responsibility, the exemplary attitude of the madrasah principal, and the provision of honoraria or incentives. Meanwhile, inhibiting factors include teachers having other jobs outside the madrasah, a lack of discipline awareness among some teachers, the absence of firm written regulations, and the non-optimal implementation of reward and punishment systems.